ASUHAN KEPERAWATAN GAWAT DARURAT PADA GAGAL GINJAL KRONIK DENGAN KELEBIHAN CAIRAN DI RUANG HEMODIALISA - Miftak Nurmaula Dewi; Resmi Pangaribuan; Jemaulana Tarigan (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Emergency Nursing (Emergency Nursing) is a comprehensive nursing given to patients with acute injuries or life threatening illness. Based on a preliminary survey conducted by researchers at the Putri Hijau Medan Kindergarten II Hospital, obtained medical record data from January to October, the number of patients who went to the Putri Hijau Medan Kindergarten II Hospital totaled 31 people consisting of outpatients and inpatients, the number of outpatient treatment was 12 people and 19 people were hospitalized. Objective: To provide emergency nursing care for chronic kidney failure with excess fluid at TK II Putri Hijau Medan Hospital. Research Methodology: This research is a descriptive study with a case study design conducted on two patients with the same diagnosis, namely the treatment of patients with Chronic Kidney Failure with fluid overload. This study uses a nursing process approach which includes the following stages: Assessment, nursing diagnosis, intervention, implementation and evaluation. Results and discussion: After taking action on the implementation of nursing care on client 1 and client 2, the evaluation stage of some problems was partially resolved on the fourth day and some others were resolved on the fourth day for each client. During 4 days of treatment for client 1 and for 4 days treatment of client 2Â then the excess fluid problem can be evaluated resolved. Conclusions and suggestions: The researchers concluded that case studies of fulfilling nursing care in patients with chronic kidney failure at Hemodialysis Hospital TK II Putri Hijau Medan were able to overcome the problem of excess fluid.